Understanding the role of a "large" family in the teaching of Pope Francis - Pyźlak, Grzegorz J. (HTS teologiese studies, 2024)
Family is perceived as the most important environment in which humans develop and satisfy their basic needs. Therefore, the issues concerning the family are still current and of great interest for numerous theoreticians and researchers of various fields of science. Pope Francis also devoted a part of his apostolic exhortation Amoris Laetitia to the issue of the ‘larger’ family. In the teachings of Pope Francis spouses and parents should make a responsible use of their freedom, both with regard to procreation, taking into account the social and demographic reality, as well as to the possibility of bringing up their offspring. Conjugal love, which, in Catholic families, is expressed in fertility, is a reason for great joy for the Church. What is innovative in the Pope’s approach to the tasks of the ‘large’ family is mainly the help provided to the people who are victims or to those who are experiencing difficulties in their family homes. Another important issue concerns proper building relations and mutual respect between people creating a ‘large’ family. To achieve this, we must remember to provide mutual assistance and recognise the dignity of each of its members as persons.Contribution: This article holds that apart from the small circle formed by spouses and their children, there is also a ‘large’ family that cannot be ignored. It is necessary for the development of the society and it is a great opportunity for their future. In the teachings of Pope Francis, it is a family that is not afraid to take on current challenges. The basic task of a ‘large’ family is to provide support and love to the people who belong to it.